Application of Vermicompost to Soil P Levels, Tissue P Levels, and Corn Yields in Entisols - Efian Aprizal; Hasanudin Hasanudin; RR Yudhy Harini Bertham; Herry Gusmara; Edhi Turmudi (TERRA : Journal of Land Restoration, 2021)
This study aims to determine the optimum dossage of vermicompost to soil P levels, tissue P levels as well as corn growth and yield in Entisols. This research was conducted at Kandang Mas village, Bengkulu City from August 2019 until November 2019. The design used in this study is Randomized Complete Block Design (RCBD) one factor is the application of vermicompost dose with three replications. The dossage of vermicompost consists of seven levels, namely 0 tons ha-1, 5 tons ha-1, 10 tons ha-1, 15 tons ha-1, 20 tons ha-1, 25  tons ha-1, and 30 tons ha-1. The results showed that there was no optimum dossage of vermicompost to soil P levels, tissue P levels, and corn yield in Entisols.